Comportamiento agronómico de ocho líneas arriñonadas de frejol (Phaseolus vulgaris L.) de la variedad EVG-6 - Salinas Mina, Jorge Augusto (2015)
This research was conducted at the Experimental Farm "La María" of the UTEQ located at km 7 Vía Quevedo - El Empalme, whose geographical coordinates are 79 ° 27 'west longitude and 01 ° 06' south latitude and 73 meters. Raised the overall objective: To evaluate kidney-shaped eight lines selected in the bush bean variety EVG-6 and specific: to determine the agronomic performance of selected lines in the range EVG-6, and determine the (s) line (s) showing the best performance per unit area. Subject to the hypothesis: Ha: At least one of the lines will have better agronomic performance and Ha: At least one line selected in the range EVG-6 has a better yield per unit area. For the development of this research, eight lines of kidney-shaped bean variety EVG - 6, plus a control (variety EVG-6). We used a completely randomized design with eight treatments and four replications. In the days to flowering was earlier the variety the EVG-6-(control), whereas in the days to maturity were earlier EVG -lines 6-118 (55.0 days) and EVG-6-127 (54.75 days). Sheath lengths of the lines EVG - 6 - 118 (13.28 cm), EVG - 6 - 160 (12.99 cm) and EVG – 6 - 249 (12.99 cm) were higher by 2.0 cm approximately EVG-line6-009. Also observed increased production of grains in the lines EVG-6-118 (4.0 grains) and EVG-6-160 (3.97 grains). The number of plants at the beginning and at harvest, plant height (cm), number of pods per plant, number of grains per plant and yield per plant (g) showed similar behavior. The yield (kg ha-1), was similar between the lines, with yields ranging between 812.7 and 1117.3 kg ha-1.